Epac1 Restores Normal Insulin Signaling through a Reduction in Inflammatory Cytokines - Elizabeth Curtiss; Youde Jiang; Li Liu; Claire Hawthorne; Jessica Zhang; Jena J. Steinle (Mediators of Inflammation)
We have previously reported that Epac1 reduced inflammatory cytokines, which is protective to the diabetic retina. We have also published that impaired insulin signaling occurs in the diabetic retina. A reduction in interleukin-1 beta (IL-1β) and tumor necrosis factor alpha (TNFα) by Epac1 could potentially restore normal insulin signal transduction. Confocal microscopy was performed to localize the insulin receptor in the retina of Epac1 floxed and endothelial cell-specific Epac1 knockout mice. Whole retinal lysates from Epac1 floxed and endothelial cell-specific Epac1 knockout mice were used to investigate proteins involved in the insulin signaling cascade. Primary human REC were cultured in normal and high glucose followed by Epac1 agonist treatment or transfection with IL-1β or TNFα siRNA for protein analyses of insulin signaling proteins. Decreased expression of the insulin receptor was observed in the Epac1 knockout mouse retinal vasculature compared to floxed littermates. Work in mice showed that loss of Epac1 decreased insulin signaling proteins. Treatment with an Epac1 agonist decreased p38 and JNK signaling and increased insulin signaling, as did inhibition of IL-1β or TNFα using siRNA when added to REC grown in high glucose. Taken together, Epac1 can restore normal insulin signaling in the retinal vasculature through reductions in inflammatory cytokines.